2009
DOI: 10.1021/jp9043804
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectroscopy of Secondary Amine Salts: 1. Assignment of NH2+Stretching Frequencies in Crystalline Phases

Abstract: The NH(2)(+) stretching modes of secondary amine salts have been previously studied, but the band assignments are inconsistent between the various studies. This paper assigns characteristic NH(2)(+) group frequencies between approximately 2500 and 2400 cm(-1). Crystal structures of four diamine salts are reported here. Vibrational frequencies were calculated with the B3LYP hybrid Hartree-Fock/density functional method and the 6-31G(d) split-valence plus polarization basis set, and the results are in agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In addition, it was proposed the theoretical model of complex Ag‐MBC based on the hybrid functional B3LYP calculation with base LanL2DZ. No scaling factor was used because studies showed that the frequency deviations are less than 5% to experimental frequencies …”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was proposed the theoretical model of complex Ag‐MBC based on the hybrid functional B3LYP calculation with base LanL2DZ. No scaling factor was used because studies showed that the frequency deviations are less than 5% to experimental frequencies …”
Section: Methodsmentioning
confidence: 99%
“…In this way, a broad band at ca. 2380 cm À1 is observed, which can be assigned to an overlap of N-H þ 2 stretching modes of secondary amines of the peptide chain [81] and S-H stretching mode of cysteines located at ca. 2500 cm À1 [82] (see Fig.…”
Section: Raman Spectroscopymentioning
confidence: 97%
“…94 Our calculations rule out the assignment of the ν[NH 2 ] modes to the features commonly occurring between approximately 2500 and 2400 cm −1 in the IR spectra. 94 Figure 4 shows convincingly that these bands stem from anharmonicity, most likely corresponding to difference bands captured by the simulations at the higher temperatures, where excitations of low-energy phonons also play a role.…”
Section: Resultsmentioning
confidence: 55%